Implementation of green accounting and environmental performance on the company's financial performance (study on companies winning the 2021 Green Industry Award) / Annisa Rahma Dania ... [et al.] - Dania, Annisa Rahma; Ekawati, Evi; Martika Sari, Yetri (Universiti Teknologi Mara Selangor, 2023)
Many environmental problems are caused by the company's operating activities which form the basis of this research, aiming to find out the application of green accounting and environmental performance to financial performance in concept rahmatan lil alamin. The method used in this research uses quantitative research methods. The population in this study are companies that are nominated to win the green industry award in 2021. The sample was selected using a purposive sampling method with three criteria which resulted in 40 companies that were worthy of observation. This study uses multiple regression analysis using the SPSS program. In this study, variables of green accounting are measured by environmental cost indicators, environmental performance variables using the PROPER rating value, and financial performance variables using ROA. Based on the results of the analysis, it shows that green accounting and environmental performance variables do not affect a company's financial performance. However, if the company has implemented green accounting then in line with the concept of Islamic economics which explains that welfare is carried out through fulfilling basic human needs, eliminating all difficulties and inconveniences, and increasing the quality of life morally and materially.